Soil temperature regimes in Finland - Yli-Halla, Markku; Mokma, Delbert L. (Agricultural Research Centre of Finland, 1998)
Amerikkalaista alkuperää olevassa maannosten luokitteluun kehitetyssä Soil Taxonomy -järjestelmässä käytetään yhtenä luokitteluperusteena maan lämpötilaa 50 cm syvyydessä. Maan lämpötila vaikuttaa varsinkin viileiden alueiden maannosten nimiin. Tämän tutkimuksen aineistona käytettiin eri lähteissä julkaistuja tietoja maan lämpötilasta Suomessa. Kun maan vuotuinen keskilämpötila on 0-8°C ja kesäkuukausina alle 15°C, maa kuuluu Soil Taxonomy -järjestelmän lämpötilaluokkaan 'cryic'. Tällaiset lämpötilaolot vallitsevat valtaosassa Suomen maaperää. Ainoa poikkeus ovat Pohjois-Lapin palsasuot. Niissä maan keskilämpötila on todennäköisesti alle 0°C ja ne kuuluvat lämpötilaluokkaan 'pergelic'.

Soil temperature regime substantially influences soil classification in Soil Taxonomy particularly in temperate areas. To facilitate correct classification of soils of Finland, the temperature regimes in soils of the country were determined. The mean annual soil temperature, measured at 50 cm below soil surface, ranged from 6.4°C at the warmest site (Anjala) to 1.9°C at the coldest one (Utsjoki, Kevo), and the mean summer soil temperature from 13.7°C to 6.2°C at the same stations, all being in the range of the cryic temperature regime. The mean annual soil temperature was 2 to 5°C higher than the mean annual air temperature, the difference (Y, °C) depending on the duration of snow coverage (X, days) according to the following equation: Y = 0.0305 X - 2.16, R2 = 0.91, n = 9. Even soils of the warmest areas in southern Finland and the mineral soils of the coldest areas in the north, at least for the most part, have cryic soil temperature regimes. Therefore, most soils of Finland, classified according to Soil Taxonomy, have names where the cryic temperature regime appears on the suborder or great group level.
Keywords: Ka; Pu; Suomi; maaperä; lämpötila; cryic temperature regime; frigid temperature regime; pergelic temperature regime; snow cover; Soil Taxonomy